ASSESSMENT OF ACCESS TO TOILET FACILITIES AND ITS HEALTH IMPLICATIONS IN TORO LOCAL GOVERNMENT AREA, BAUCHI STATE, NIGERIA - WAMBAI, MUSA WOKTONG; ALI, ANDESIKUTEB YAKUBU; EZRA LEKWOT VIVAN; DALOENG, HYACINT MADAKI; OBASI, MERCY TABI; GIWA, CLEMENT YAKUBU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Nigeria occupies the second position in global open defecation rating and poor access to toilets in the country has been attributed to economic, cultural and social norms as many people still defecate in the open space, bushes and rivers. The objectives of this study were to assess the level of accessibility to improved toilet facilities, examine the health impacts of poor toilets and to find out the respondents’ perception on the benefits of improved toilet facilities. The descriptive survey method normally employed for public opinion surveys, fact finding surveys and status studies among others was used for this study. Systematic sampling technique was employed for the selection of the study settlements and the respondents. Descriptive statistics which provides a concise numerical summary of the characteristics of a variable was used in the analysis of the data collected for this study. The findings of this study reveal that 52.66% of the respondents earned less than NGN220 per day out of which 23.11% have daily income of less than NGN110. Whereas only 2.95%had access to improved toilets, 61.57% use pit latrine which is not safe. The noble perception of the respondents that improved toilet facilities prevent diseases is hijacked by poverty and ignorance. Access to improved toilet facilities could be achieved through vigorous public enlightenment programmes by stakeholders and economic empowerment to heads of household by Government, NGOs and philanthropies.